Efektivitas Penerapan Program Evaluation and Review Technique (PERT) Dalam Perencanaan Pendidikan - Fikri Hamdi Siregar; Khalisatun Husna; Nurul Atika Hasibuan; Abdul Fattah Nasution (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Effective educational planning requires a data-driven approach to optimize time, resources, and decision-making. Program Evaluation and Review Technique (PERT) is a project management method that can support this, especially in large-scale educational projects. This study aims to evaluate the effectiveness of PERT in educational planning, with a focus on time optimization, resource efficiency, and data-based decision-making. The method used is a literature study, by reviewing various library sources such as journals, books, and research reports. The results of the study indicate that PERT is able to reduce project implementation time, improve resource efficiency and PERT supports data-based decision-making. In conclusion, PERT is an effective method to improve the efficiency and effectiveness of educational planning. Successful implementation requires training, technology support, and good coordination between stakeholders.